The Effect of Trunk Stability Training on Increasing Segmental Values ​​of Trunk Control in Cerebral Palsy Patients - Siti Sarah Bintang; Elvida Rahmi; Helvi; Rizka Mutiara; Karnirius Harefa (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cerebral palsy (CP) is the most common cause of physical disability in children. One of the most frequently cited definitions of CP is 'a group of permanent disorders in the development of movement and posture, which causes activity limitations, caused by non-progressive disorders that occur in the development of the fetal or infant brain'. Non-pharmacological approaches such as exercise therapy have been shown to be effective in overcoming the problems of children with cerebral palsy. One of the exercise interventions that has the potential to increase trunk stabilization is Treatment Trunk Stability Training. This technique works synergistically to target the trunk, improve gross motor function, trunk control, and balance, and will help better functional recovery in children with cerebral palsy. Objective: To determine the effect of Trunk Stability Training on Increasing Segmental Of Trunk Control Values ​​in Cerebral Palsy Patients. Methods: This study is a quantitative pre-experimental study with a one group pretest-posttest design. A total of 13 subjects diagnosed with cerebral palsy underwent a two-week intervention. Measurement of trunk stability or trunk control was performed using Segmental Of Trunk Control (SATCo). Data analysis used the Wilcoxon Signed-Rank test with a significance level of α = 0.05. Results: The results of the Shapiro-Wilk normality test showed that the data were not normally distributed (p <0.05). The results of the Wilcoxon test showed a p-value = 0.016 (<0.05), which means that there was a significant difference between the Segmental Of Trunk Control (SATCo) scores before and after the intervention. Conclusion: Trunk Stability Training treatment has been proven effective in strengthening or stabilizing the trunk/torso and improving trunk control in children with cerebral palsy.